2019
DOI: 10.2147/cmar.s213580
|View full text |Cite
|
Sign up to set email alerts
|

<p>The prognostic value of the postoperative serum CEA levels/preoperative serum CEA levels ratio in colorectal cancer patients with high preoperative serum CEA levels</p>

Abstract: Purpose This study aimed to assess the prognostic value of the postoperative serum carcinoembryonic antigen (CEA) levels/preoperative serum CEA levels ratio (CEA ratio) in colorectal cancer (CRC) patients with high preoperative serum CEA levels and to identify the optimal prognostic cutoff value. Patients and methods The medical records of 187 CRC patients in a single center who underwent surgery between September 2012 and September 2014 were retrospectively reviewed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…It is accepted that TNM staging is the most reliable criterion for assessing CRC patient prognosis. However, it has been reported that patients with the same TNM stage often have different prognoses, suggesting that other factors are required for more accurate prognoses (Xie et al, 2019). We conducted a stratified prognostic evaluation based on different TNM stages, and found that survival outcomes of different ALI groups were significantly different in patients with TNM III-IV stage, but there were no differences in patients with TNM I-II stage.…”
Section: Discussionmentioning
confidence: 89%
“…It is accepted that TNM staging is the most reliable criterion for assessing CRC patient prognosis. However, it has been reported that patients with the same TNM stage often have different prognoses, suggesting that other factors are required for more accurate prognoses (Xie et al, 2019). We conducted a stratified prognostic evaluation based on different TNM stages, and found that survival outcomes of different ALI groups were significantly different in patients with TNM III-IV stage, but there were no differences in patients with TNM I-II stage.…”
Section: Discussionmentioning
confidence: 89%
“…Elevated preoperative CEA levels are associated with advanced cancer stage, the incidence of recurrence, and survival. Also, high postoperative CEA levels are associated with residual disease and/or distant metastasis [24,25]. In colon cancer, it is important to predict patient prognosis and detect any early recurrence, thus efforts are being made to identify prognostic factors [22,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that left-sided colon cancer is associated with improved survival [3], suggesting that tumor sidedness could be an important prognostic factor. While postoperative serum carcinoembryonic antigen (CEA) level is routinely used as a marker for possible metastatic disease, the perioperative CEA ratio (post-op/pre-op CEA) may be an important emerging prognostic factor for CRC patients [4,5] and may be especially important in patients with high preoperative CEA levels [6]. To our knowledge, the association between perioperative CEA ratio and tumor location has not been previously established.…”
Section: Introductionmentioning
confidence: 99%